[Comment] Stoma versus anastomosis after sphincter-sparing rectal cancer resection;the impact on health-related quality of life - Xu Rong; Tong Weihua (结直肠肛门外科)
[Background] Surgical resection is the mainstay of curative treatment for rectal cancer. Post-operative complications, low anterior resection syndrome (LARS), and the presence of a stoma may influence the quality of life after surgery. This study aimed to gain more insights into the long-term trade-off between stoma and anastomosis. [Methods] All patients who underwent sphincter-sparing surgical resection for rectal cancer in the Leiden University Medical Center and the Reinier de Graaf Gasthuis between January 2012 and January 2016 were included. Patients received the following questionnaires: EORTC-QLQ-CR29, EORTC-QLQ-C30, EQ-5D-5L, and the LARS score. A comparison was made between patients with a stoma and without a stoma after follow-up. [Results] Some 210 patients were included of which 149 returned the questionnaires (70.9%), after a mean follow-up of 3.69 years. Overall quality of life was not significantly different in patients with and without stoma after follow-up using the EORTC-QLQ-C30 (p = 0.15) or EQ-5D-5L (p = 0.28). However, after multivariate analysis, a significant difference was found for the presence of a stoma on global health status (p = 0.01) and physical functioning (p < 0.01). Additionally, there was no difference detected in the quality of life between patients with major LARS or a stoma. [Conclusion] This study shows that after correction for possible confounders, a stoma is associated with lower global health status and physical functioning. However, no differences were found in health-related quality of life between patients with major LARS and patients with a stoma. This suggests that the choice between stoma and anastomosis is mainly preferential and that shared decision-making is required.